2013
DOI: 10.1590/s1415-65552013000600005
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing local government financial performance: evidence from Brazilian municipalities 2005-2008

Abstract: Municipality size has become an issue since the New Public Management doctrine of disaggregating structures into manageable units. In some countries, this doctrine led to the creation of small-scale agencies relying heavily upon transfers from upper-level governments. This paper aims to contribute to performance management literature by providing empirical evidence about some determinant factors that are likely to endow local governments with superior financial performance. Data came from a sample of Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 39 publications
1
29
0
13
Order By: Relevance
“…The financial performance management index (FPMI) showed the lack of self sufficiency of the 122 local governments as the ratio is far less than one. Reference [12] suggest that as the FPMI approaches zero, the more the reliance of the local government on transfers from higher government authorities. Thus, none of the local governments showed good financial performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The financial performance management index (FPMI) showed the lack of self sufficiency of the 122 local governments as the ratio is far less than one. Reference [12] suggest that as the FPMI approaches zero, the more the reliance of the local government on transfers from higher government authorities. Thus, none of the local governments showed good financial performance.…”
Section: Resultsmentioning
confidence: 99%
“…For example, self income ratios, financial performance index, ratio of percentage change in net assets to total assets, and fiscal balance [8,12,17]. Similarly, this study utilized four ratios: fiscal balance ratio, financial performance index, self income ratio, and budget solvency ratio in examining the financial condition of local governments in Nigeria.…”
Section: Financial Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study examines performance in terms of the effectiveness of local government service provision. Unlike previous studies of municipal performance in Brazil that focus on the financial aspects of performance, such as property tax collection (Avellaneda & Gomes, 2015) or financial management and self-sufficiency (Gomes, Alfinito, & Albuquerque, 2013), our performance measure captures the effectiveness of local governance or "the actual achievement of formal service objectives" (Walker & Andrews, 2015, p. 103). These nine outcomes are useful for analyzing the effects of audits on municipal performance because they fall under the broader jurisdiction of municipal governments and may be subject to investigation during an audit.…”
Section: Dependent Variable: Aggregate Municipal Performancementioning
confidence: 99%
“…Results indicated that higher levels of education indicate an increase in government strategic performance, while age and tenure have no effect on improving strategic performance of local governments. Gomes et al (2013) conducted research on the quality of mayors proxied against educational background, age, previous administrative experience and city size on the financial performance of Brazilian local Advances in Economics, Business and Management Research,volume 36 governments. The results showed that the quality of the mayor does not affect the government's financial performance.…”
Section: Introductionmentioning
confidence: 99%